Isomer effect on the near-infrared electrochromism of anthraquinone imides. (1st June 2015) - Yao, Bin; Chen, Fengkun; Jiang, Hong; Zhang, Jie; Wan, Xinhua
Graphical abstract: Highlights: Two pairs of unsubstituted isomers (Ia andIb ) and nitro-substituted isomers (IIa andIIb ) of anthraquinone imides (AQIs), which are a unique type of cathodically-colouring NIR electrochromic materials bearing both quinone and imide moieties, were synthesized. Isomer effect on the NIR electrochromism of n-type optoelectric materials was first approached. A meaningful reference to design cathodically active NIR EC materials, in which the molecular planarity and the orientation of polar groups are two key elements must to be carefully considered, is provided. Abstract: To deeply explore the interplay between molecular structure and near-infrared electrochromism of anthraquinone imides, two pairs of unsubstituted isomers (Ia andIb ) and nitro-substituted isomers (IIa andIIb ) of anthraquinone imides were synthesized, in which the moleculesIa andIIa took more linear shapes thanIb andIIb . Cyclic voltammetry and spectroelectrochemistry were combined to investigate their electrochemical properties. Cyclic voltammetry showed thatIb andIIb revealed decreased first reduction potentials and low cyclic stability compared to their isomers, indicating that the isomerization weakened the stabilization effect. Upon one-electron reduction, both the absorption wavelengths and absorption intensities of radical anions were greatly dependent on the structures of isomers. The radical anions ofIa, IIa, andIIb illustrated NIR absorptions peaked at 820, 1260, and 1380 nm, respectively, but that ofIb exhibited only weak absorption in the visible region centered at 660 nm. Gaussian calculations suggested that the electrons were delocalized over the whole molecular skeletons ofIa andIIa radical anions, but the effective conjugation length was interrupted on the imide section in bothIb andIIb . The isomer effects on the effective conjugation length and electron density distribution were considered to rationalize the different electrochromic behaviors.